Dangerous liaisons?: A feminist and restorative approach to sexual assault - Pali Brunilda; Sten Madsen Karin (Temida, 2011)
The appropriateness of restorative justice (RJ) for gendered violence offences such as domestic violence and sexual assault has always been and still is highly contested. This paper focuses on the appropriateness of RJ measures in addressing sexual assault, primarily with reference to experience of restorative dialogues as practiced at the Centre for Victims of Sexual Assault in Copenhagen, and it takes a feminist approach to the application of RJ measures to sexual assault. Within this framework, the paper tackles two issues in particular: the privacy element of RJ versus the public aspect of the criminal justice system (CJS), and the intersection of the CJS and RJ in cases of sexual assault. In relation to the relationship between CJS and RJ, the authors argue that RJ could be used for victims of sexual assault, not primarily as part of diversion programmes, but when offered apart from and/or parallel to the CJS. In relation to the private/public debate, the authors argue that while RJ encounters, by taking place in highly confidential settings, might have a negative impact on efforts by women’s movements to move violence against women out of the private and into the public realm, creating high standard alternatives for individual women who are in need of support and constantly generating public debate about gendered violence is a good feminist response to this complex issue.